Perancangan Database Karyawan Kontrak Berbasis Visual Basic dan Excel : Studi Kasus Badan Kepegawaian dan Sumber Daya Manusia - Kristia Yuliawan; Jevan Pilenaung (STMIK Pesat Nabire, 2024)
Managing contract employee data is an important aspect in maintaining employee productivity and well-being in an organization or company. This research aims to design a database that can manage contract employee data effectively and efficiently. Using the prototyping method, this research involves several stages, namely problem formulation, data collection, system analysis, and system development. Data is collected through surveys, interviews, and observations, then analyzed to understand the needs of the system. Initial prototypes are developed and evaluated to ensure conformity to user needs. The designed database allows for centralized and structured storage of employee data, facilitates data access and updates, improves data consistency and accuracy, and improves security and ease of data analysis. Testing is carried out by black-box method to ensure system functionality. The test results show that the system can manage contract employee data well, meet user needs, and provide support for better decision-making in human resource management. The study concludes that integrated and well-documented management of contract employee data can improve operational efficiency and support organizational success.